REMEDIASI KESULITAN BELAJAR TENTANG USAHA BERBASIS EXPERIENTIAL LEARNING PESERTA DIDIK SMA NEGERI 3 PONTIANAK - Valentin Minarti Agata; Haratua Tiur Maria Silitonga; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aimed to assess the effectiveness of learning difficulties using the experiential learning model to remediate the number of students that have misconception and errors in completing problems on work at SMAN 3 Pontianak. The method used in this research was a pre-experimental design with one group pre-test post-test design. Samples of study were intact group and selected based on physics teacher’s recommendation. The research instruments included 10 questions of diagnostic test and 6 questions of essay test. The percentage number of students with misconceptions of each indicator and student was reduced to 56.19% and 35.87%. Based on the results of the McNemar test, overall students experienced significant conceptual changes with a value of χ2 count (84.27)> χ2 table (3.84), df = 1 and α = 5%. The percentage decreased by 59,78% in the number of errors in completing problems for each student. Based on the results of the Normality test and Wilcoxon test, overall students experienced differences or decreased errors in completing problems with Asymp. Sig. (2-tailed) of 0.000 so that Ho was rejected. The effectiveness for both experiental learning model to remediate the number of student’s misconception on work through DQM of 56.20% and the effectiveness to reduce the errors of students in completing problems through a decrease proportion was 0.53 which are included to medium category. Therefore, this research is suggested to be use as an alternative learning activity to reduce the number of students that have learning difficulties on work.Keyword: Experiential Learning, Learning Difficulties, Misconception, Remediation, Work.